2015
DOI: 10.1111/nph.13720
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus cycling in deciduous forest soil differs between stands dominated by ecto‐ and arbuscular mycorrhizal trees

Abstract: SummaryAlthough much is known about how trees and their associated microbes influence nitrogen cycling in temperate forest soils, less is known about biotic controls over phosphorus (P) cycling. Given that mycorrhizal fungi are instrumental for P acquisition and that the two dominant associations -arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) fungi -possess different strategies for acquiring P, we hypothesized that P cycling would differ in stands dominated by trees associated with AM vs ECM fungi.We q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
110
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 75 publications
8
110
4
1
Order By: Relevance
“…as soil carbon storage (34), nitrogen leaching (35), and phosphorus cycling (36). Here, we provide additional evidence that the relative dominance of AM or EM trees in a forest, as well as their root traits, may partly determine the response pathways (roots vs. hyphae) to fine-scale spatial heterogeneity of soil nutrients.…”
Section: Resultsmentioning
confidence: 66%
“…as soil carbon storage (34), nitrogen leaching (35), and phosphorus cycling (36). Here, we provide additional evidence that the relative dominance of AM or EM trees in a forest, as well as their root traits, may partly determine the response pathways (roots vs. hyphae) to fine-scale spatial heterogeneity of soil nutrients.…”
Section: Resultsmentioning
confidence: 66%
“…The mycorrhizal symbiosis then both constrains plant growth but also prevents non‐mycorrhizal plants being able to invade such forests (Näsholm et al ., ; Franklin et al ., ). However, despite strong P limitation the forests described by Rosling et al . are surprisingly productive, to judge from data on annual litter fall.…”
contrasting
confidence: 59%
“…Rosling et al . observed that in these forests ectomycorrhizal and arbuscular mycorrhizal tree growth was equally limited by P. There were no differences in plant P uptake from, or plant P return to, the soil. Both mycorrhizal forests harboured a similar microbial biomass (of symbiotic and saprotrophic microbiota), a pool that contained almost three times as much P as the annual P uptake by the vegetation.…”
mentioning
confidence: 97%
“…If this is the case, the frequency of the ECM plant type is expected to increase under future global change scenarios (Tedersoo, ). Thus, the correlation patterns identified here suggest that such a process would be accompanied by decreases in the diversity and abundance of AM fungal and plant species, which could have profound effects on ecosystem functioning, such as carbon, nitrogen and phosphorus cycling (Fernandez & Kennedy, ; Lin, McCormack, Ma, & Guo, ; Rosling et al, ; Treseder & Lennon, ). In the future, there is a need to complement correlative studies with empirical tests concerning the quadripartite competition between ECM and AM symbiotic partners, and interactions involving ERM and NM partners, in order to better understand the distribution of mycorrhizal types and predict their responses to global change.…”
Section: Discussionmentioning
confidence: 88%